HPTLC Estimation of Nateglinide in Bulk Drug and Tablet Dosage Form - Kale, D.L.; Kakde, R.B. (Asian Journal of Chemistry, 2011)
A simple, accurate and precise HPTLC method has been developed and validated for estimation of nateglinide in bulk drug and tablet formulation. Nateglinide from the formulation was separated on silica gel 60 F254 HPTLC plates with n-hexane, methanol and 2-propanol in the proportion of 7.5:1.5:1 (v/v) as the mobile phase. Densitometric quantification was performed at 210 nm. Band obtained with Rf value 0.56 ± 0.02 for nateglinide. The method was validated in accordance with the requirements of ICH guidelines. The calibration curve found to be linear in the range of 300-1000 ng/band both by area and height with r = 0.9994, 0.9998, slope = 0.121, 3.344 and intercept = 22.039, 250.629, respectively. The limit of detection and limit of quantification both by area and height were 78.95, 33.55 and 236.84, 100.64 ng per band, respectively. The result of estimation was found to be 98.49 ± 0.32 in Glinate tablet. The proposed method can be used successfully for routine analysis of nateglinide from bulk and tablet formulations.